Jackpot - Stone, Nic (Ember, 2020)
Meet Rico: high school senior and afternoon-shift cashier at the Gas 'n' Go, who after school and work races home to take care of her younger brother. Every. Single. Day. When Rico sells a jackpot-winning lotto ticket, she thinks maybe her luck will finally change, but only if she--with some assistance from her popular and wildly rich classmate Zan--can find the ticket holder who hasn't claimed the prize. But what happens when have and have-nots collide? Will this investigative duo unite ... or divide in this hard-hitting story about class, money--both too little and too much--and how you make your own luck in the world
Keywords: High school students / Fiction; Lotteries / Juvenile fiction; Social classes / Juvenile fiction; Popularity / Juvenile fiction; Families / Georgia / Norcross / Fiction; Norcross (Ga.) / Fiction; Young adult fiction; Élèves du secondaire / Romans, nouvelles, etc; Loteries / Romans, nouvelles, etc. pour la jeunesse; Classes sociales / Romans, nouvelles, etc. pour la jeunesse; Popularité / Romans, nouvelles, etc. pour la jeunesse; Roman pour jeunes adultes; Families; High school students; Lotteries; Popularity; Social classes; Georgia / Norcross; Lotteries / Fiction; Social classes / Fiction; Popularity / Fiction; Family life / Norcross (Ga.) / Fiction; Fiction; Juvenile works; Romance fiction; Young adult works